Constitutional mechanisms for human rights protection in Vietnam’s socialist-law governed state - Hoang, Van Nghia (Đại học Quốc gia Hà Nội, 2020)
The main goal of this paper is to identify the Constitutional Mechanism for the Protection of Human Rights in the Socialist law-governed state of Vietnam today through assessing the concept, substances and the interrelationship between Constitution, human rights and the rule of law, both in theory and practice in Vietnam today. Since the 1st Constitution of 1945, Vietnamese legal system in general and constitional rights have been developed and contributed significantly to the development of constitutionalism, rule of law and good governance, and in its turn, the consistent improvement of the respect for, protection and promotion of human rights for all in Vietnam. However, constitutional rights need constitutional mechanisms for their implementation and realization. Utilizing the casestudy approach, the paper analyzes, interprets and clarifies the relationship, role, position and characteristics of constitutionalism, rule of law and human rights, as well as their mechanisms for protection, in the viewpoints of a socialist law-governed (rule-of-law) state. The paper assesses the achivement of constitutionalizing, as well as legalizing human rights, especially the right to access to information. The paper clarifies some inadequacies and limitations of the application of constitutional rights in practice. At the same time, the paper proposes some recommendations for the development and improvement of the mechanisms for constitutional and human rights protection in the model of the socialist law governed state in Vietnam today.